The effect of computer aided education program on the development of concept in 48-60 months children - BALABAN DAĞAL, ASUDE; UYANIK, GÜLDEN; KANBUROĞLU, VOLKAN (ELSEVIER SCIENCE BV, 2015)
Children gain the most important basic concepts which help them understand and know about life, during preschool education. According to Manocha and Narang (2004) concepts are the basic units of all types of learning. Human beings from the infancy to old age learn new concepts and use old concepts in new situations of their daily life. Individuals differ in their level of concept formation depending on their age, intelligence and experience. The aim of the present study was to examine the effectiveness of the computer aided education (CAE) in making 48-60 months children who attend preschool education institutions to gain the concept of position in space. 109 children, who were 48-60 months of age and who attended four different classes in two different primary schools in Istanbul, have participated to the study. In the study, a pre-test post-test control group design was used. Computer-aided education training program for teaching the concepts of position in space prepared by Uyanik Balat and Kanburoglu (2009) was applied individually to each child in the study. To measure the development of concepts of position in space, BOEHM Test of Basic Concept (BOEHM-3) was applied to both groups before and after the computer-aided education program. The study revealed significant difference between the pre-test and post-test scores for both of the experimental and control groups. The difference between the post-test scores of the experimental and control group are seen to be significant in favor of the experimental group. Accordingly it can be said that the computer aided education (CAE) is effective in making 48-60 months children to gain the concept of position in space. Results are discussed in line of other related researches. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Computer aided concept education; preschool; position in space concepts